Studi Tentang Penerapan Character Building Di Sekolah Dan Madrasah - Arif Shofwan (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2022)
This qualitative research discusses character building in schools and madrasas. This literature study focuses on three things, namely the application of character building; the role of the teacher, as well as supporting and inhibiting character formation. This research resulted in the following things. First, the application of character building can be done by using eighteen cultural values ??and national character formulated by Indonesian national education and others. Second, the role of teachers in character building, including: evaluators, motivators, counselors, mentors, and mediators for the formation of the character of students to the fullest. Third, supporting factors for character building, including: pre-school experience, level of intelligence, creativity, learning motivation, attitudes and study habits, and a positive school environment. Fourth, the inhibiting factors for character building include: the strong influence of behaviorism in the education system, the low capacity of human resources for educators, the demands of an increasingly pragmatic era, attitudes and stances that are less favorable for the establishment of democratization of education, and several other things. Keywords: Character Building, Education, Schools, and Madrasas